1980
DOI: 10.1021/ja00521a036
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of formation of Grignard reagents. Kinetics of reaction of substituted aryl bromides with magnesium and with tri-n-butyltin hydride in ethereal solvents

Abstract: Whitesides et al. / Reaction of Substituted Aryl Bromides with Magnesium23 1 clohexane of s for CH3Br-. and 3 X lo-* s for CH3CI-. (P. P. lnfelta and R. H. Schuler, J. phys. Chem., 76,987 (1972)). If these data are Correct, alkyl bromides and alkyl chlorides might react by different initial steps.(14) Radical chain reactions are usually detected by rate inhibitions resulting from addition of free-radical scavengers. Any reactions involving freeradical chains in this system must be fast to be compatible with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…A conceptually related set of studies [1,2,[36][37][38][39] , with entirely different mechanistic problems, concerned the mechanism of formation of Grignard reagents by the reaction of organic halides with metallic magnesium in ethereal solvents. Studies of stereochemistry and product revealed that this heterogeneous reaction proceeded predominantly by electron transfer [36][37][38][39] , followed by reaction of the resulting organic free radical with the surface of magnesium, and made it possible to define some of the characteristics of the corrosion reaction that removed magnesium atoms from the bulk metal. (It thus used vpc to determine important elements of a very rapid reaction occurring at a reactive metal surface.)…”
Section: (Eq 4)mentioning
confidence: 99%
“…A conceptually related set of studies [1,2,[36][37][38][39] , with entirely different mechanistic problems, concerned the mechanism of formation of Grignard reagents by the reaction of organic halides with metallic magnesium in ethereal solvents. Studies of stereochemistry and product revealed that this heterogeneous reaction proceeded predominantly by electron transfer [36][37][38][39] , followed by reaction of the resulting organic free radical with the surface of magnesium, and made it possible to define some of the characteristics of the corrosion reaction that removed magnesium atoms from the bulk metal. (It thus used vpc to determine important elements of a very rapid reaction occurring at a reactive metal surface.)…”
Section: (Eq 4)mentioning
confidence: 99%
“…Whitesides and coauthors have carried out competitive kinetics studies (rates relative to a reference cyclopentyl bromide substrate) using different types of magnesium (turnings or rods or powder) and alkyl and aryl halides substrates. They reported the influence of different substituent and solvent on the relative rates of reactions of aryl halides with magnesium.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic studies of the reaction were conduct ed in many investigatio ns [8][9][10][11][12][13][14][15]. Products and intermedia tes of the reaction between magnesium and hydrocarb on halides were charac terized [6,[15][16][17][18], the morphol ogy of a metallic surface after the reaction was investigate d [19].…”
Section: Introductionmentioning
confidence: 99%